Characterization of diverse Cas9 orthologs for genome and epigenome editing - Gabriel L. Butterfield; Dahlia Rohm; Avery Roberts; Matthew A. Nethery; Anthony J. Rizzo; Daniel J. Morone; Lisa Garnier; Nahid Iglesias; Rodolphe Barrangou; Charles A. Gersbach (Proceedings of the National Academy of Sciences, 2025)
CRISPR-Cas9 systems have revolutionized biotechnology, creating diverse new opportunities for biomedical research and therapeutic genome and epigenome editing. Despite the abundance of bacterial CRISPR-Cas9 systems, relatively few are effective in human cells, limiting the overall potential of CRISPR technology. To expand the CRISPR-Cas toolbox, we characterized a set of type II CRISPR-Cas9 systems from select bacterial genera and species encoding diverse Cas9s. Four systems demonstrated robust and specific gene repression in human cells when used as nuclease-null dCas9s fused with a KRAB domain and were also highly active nucleases in human cells. These systems have distinct protospacer adjacent motifs (PAMs), including AT-rich motifs and sgRNA features orthogonal to the commonly used Staphylococcus aureus and Streptococcus pyogenes Cas9s. Additionally, we assessed gene activation when fused with the p300 catalytic domain. Notably, S. uberis Cas9 performed competitively against benchmarks with promising repression, activation, nuclease, and base editing activity. This study expands the CRISPR-Cas9 repertoire, enabling effective genome and epigenome editing for diverse applications.